Determinant Factors of Visiting Antenatal Care among Pregnant Mothers In Dictor Public Health Center, Manggarai Regency - Reineldis Elsidianastika Trisnawati; Pius Weraman; Stefanus P. Manongga (International Journal of Nursing and Health Services (IJNHS), 2021)
Health care services to pregnant mothers is conducted by health professionals mainly midwives in health care facilities. Midwivery care is an important effort to achieve optimal mother health and minimize mother’s morbidity and mortality risk. The objective of this study was to analyze determinant factors of antenatal care (ANC) visit of pregnant mothers in Dintor Public Health Center, Manggarai Regency. This study used analytic study design with cross sectional approach. The respondents of this study is 56 post partum mothers, recruited with nonprobability sampling technique, total sampling were conducted. Data were collected through questionnaire, analyzed using logistic regression test with significant value ?=0,05. The study result showed the existence of influence of mother’s age (p= 0,029), parity (p= 0,027), education (p=0,007), working status (p= 0,000), knowledge (p= 0,000) and ANC quality of care (p= 0,012) towards the pregnant mother’s ANC visit. Based on the multivariate analysis result, the most significant variable influencing pregnant mother’s ANC visit in Dintor Public Health Center was mother’s education variable with odds ratio=25.946, ANC quality of care with odds ratio =28.241, working status with odds ratio=18.260, while knowledge variable was insignificantly influencing on the collective test with p value>0.05. It was concluded that all the variables tested in this study determining the pregnant mother’s ANC visit on Dintor Public Health Center. Thus, health workers particularly midwives expected to improve the promotive effort through health education on the importance of regular pregnancy examination in order to monitor mother and baby’s health